The management of tea research - Huq, Mainul (Cranfield University, 1996)
Sponsors and clients of agricultural R&D are showing increasing concern about research costs and benefits. R&D organisations need to assess the impact of research to justify spending, obtain continuous technical and financial support from donors, and research sponsors. Further, impact assessment for R&D organisations are essential to assess their management systems in order to optimise the benefits from scarce research resources. At present criteria to assess the performance, objective verifiable indicators and means of verification are not available. No systematic method is in practice to assess the research management performance. Therefore, a study was under taken to develop tea R&D management criteria and incorporated these in a methodology to assess performance of research management in the tea sector. A case study approach was adopted. Six case studies were conducted on Tea Research Institutes of Asia and Africa. Case studies were grouped into two phases. Phase One was exploratory in nature and developed the conceptual framework for the research. This enabled the identification of research management criteria, objective verifiable indicators and means of verification. These can be used to improve in R&D management decision making. In addition, a scoring model was developed to assess the performance of research management in tea. Phase Two applied the developed conceptual model to four tea R&D organisations and analysed their performance. This clearly showed that the identified criteria and developed conceptual model can be used to analyses the performance of tea R&D management. Results indicated that there is lack of a structured approach to organising and conducting R&D activities. Research is carried out without any systematic approach for research prioritisation. Appraisal and resource allocation are inadequately addressed. Management information systems for rational, quick and effective decision making for the most part are weak and unorganised. Data on resource utilisation and benefits derived by individual research projects are rarely recorded and maintained properly. There is a lack of general awareness especially regarding importance of studying the rate of uptake of technology. A good correlation, however, was observed between organisations adopting best practices and suggested guidelines and the performance of tea R&D organisations in terms of perceived benefit to the client industry. The most effective R&D was associated with committee culture, problem identification, monitoring, evaluation, publication, technology dissemination and feedback. The developed model was applied in specific context of Bangladesh Tea Research Institute. Specific suggestions are made on how to improve the linkages with the industry, better ways of problem identification, evaluation and technology dissemination, and there by increased contribution to the productivity of the tea sector. A research management cycle (RPCM) was developed which proposes to carry out research in an organised way emphasising the participation of the beneficiary. Best practices for all the identified criteria and guidelines for major research management criteria were developed to support in R&D decision making. The study recommends further work to monitor and evaluate the application of the guidelines in practice.